The unique role of the associative thalamus in cognitive processing - Bin A. Wang; Shumei Li; Michael M. Halassa; Burkhard Pleger (Brain Research Bulletin)
The thalamus, centrally located in the forebrain, has traditionally been recognized as a relay station for sensory and motor signals. Recent research has challenged this perspective by revealing previously unrecognized functions, such as regulating cortical excitability, maintaining the balance between excitation and inhibition, and modulating effective connectivity. These non-relay functions stem from genuine thalamic processing of a wide range of inputs that lead to contextual signals that play a role in advanced cognitive abilities underpinning learning, attention, and executive functions. Particularly, associative thalamic structures, such as the mediodorsal thalamus and pulvinar which receive driving inputs from the cortex and participate in transthalamic cortico- cortical loop, play a crucial role in enhancing information processing efficiency for higher cognitive functions. This paper reviews recent advances in thalamic research, with a focus on the pulvinar and mediodorsal thalamus and their integrative role in cognitive processing. We discuss the computational principles of these transthalamic interactions revealed by the neural network models. We additionally summarize recent evidence on how thalamic dysfunctions contribute to mental disorders, using schizophrenia as a key example, and highlight the potential of targeting the associative thalamus for novel diagnostic and therapeutic strategies. This review combines findings from both animal models and human studies, providing a comprehensive overview of the diverse contributions of the thalamus to cognition and its potential to revolutionize mental health treatment through a multidisciplinary perspective.